Cuantificación del contenido de polifenoles totales del fruto de Passiflora tripartita var. mollissima. "pur pur" - Rodríguez Solano, Karent Paola (2017)
The present study aimed to quantify the total polyphenol content of Passiflora tripartitea var. mollisima "pur pur" from the district of Lucma, province of Gran Chimú, La Libertad region. A specimen of the plant species was duly identified in the Herbarium Truxillense (HUT). From the juice of the fruits, the ethanolic extract 50 °GL was prepared by refluxing. Total polyphenols were quantified by the Folin-Cicalteau method using UV-visible spectrophotometry. The results reported were 1.349 g tannic acid / 100 g Fresh fruit